A political economy analysis of liquid fuel production incentives in South Africa - Lott, Tawney (Energy Research Centre, 2018)
The purpose of this study is to analyse the development of South Africa's liquid fuels industry from 1930s to the present and the various ways in which the state has extended subsidies and other measures of support to liquid fuels producers. The nature and extent of government support to the South African liquid fuels industry has remained hidden for many years, due to the veil of secrecy surrounding the industry prior to the country's transition to democracy. The study expands past analyses to identify and estimate the magnitude of subsidies to liquid fuels production in South Africa in the present. Using the historical institutional approach, the study then places these measures of support in the South African political economy environment so as to understand the institutional barriers to their reform. In doing so, the study sheds light on the drivers informing the endurance of the liquid fuels subsidy regime and state support to the liquid fuels industry following the transition to democracy.